2018
DOI: 10.1080/19390211.2017.1406427
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Radioprotective Effect of Tomato Seed Oil Against Gamma Radiation–Induced Damage in Male Rats

Abstract: Radiation protection research receives intense focus due to its significant impact on human health. The present study was undertaken to investigate the protective effect of pretreatment with tomato seed oil (TSO) against gamma radiation-induced damage in rats. Male Wistar rats were divided into four groups: (1) untreated control; (2) TSO-supplemented; (3) gamma-irradiated; (4) TSO-pretreated and gamma-irradiated. Acute exposure of animals to a single gamma radiation dose (6 Gy) induced oxidative stress in majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The strongest evidence for the essentiality of RONS in breast cancer from IR comes from studies, showing that reducing RONS with antioxidants including catalase or SOD or NOX/DUOX inhibitors also reduces downstream key events including DNA damage and GI in multiple types of irradiated cells and bystander cells in vivo and in vitro after IR (Ameziane- El-Hassani et al 2010Azzam et al 2002;Bensimon et al 2016;Choi et al 2007;Dayal et al 2008Dayal et al , 2009Douki et al 2006;Jones et al 2007;Manna et al 2015;Ozyurt et al 2014;Pazhanisamy et al 2011;Tartier et al 2007;Tian et al 2015;Weyemi et al 2015;Winyard et al 1992;Yang et al 2007bYang et al , 2005, while inhibiting NO in particular inhibits DNA damage and mutations in bystander cells (Han et al 2010;Tartier et al 2007;Yang et al 2007b;Zhou et al 2008). Antioxidant activity also reduces the inflammatory response to IR in animals and cultured skin cells (Berruyer et al 2004;Das et al 2014;Ezz et al 2018;Haddadi et al 2017;Khan et al 2015;Ozyurt et al 2014;Sinha et al 2011Sinha et al , 2012Zetner et al 2016;Zhang et al 2017) and the epigenetic effects of IR in vitro (Bernal et al 2013;Kloypan et al 2015;Simone et al 2009). RONS also drives proliferation directly (Han et al 2010) and via cell death and compensatory proliferation following damage to DNA and important cellular macromolecule...…”
Section: Essentiality Of Ronsmentioning
confidence: 99%
“…The strongest evidence for the essentiality of RONS in breast cancer from IR comes from studies, showing that reducing RONS with antioxidants including catalase or SOD or NOX/DUOX inhibitors also reduces downstream key events including DNA damage and GI in multiple types of irradiated cells and bystander cells in vivo and in vitro after IR (Ameziane- El-Hassani et al 2010Azzam et al 2002;Bensimon et al 2016;Choi et al 2007;Dayal et al 2008Dayal et al , 2009Douki et al 2006;Jones et al 2007;Manna et al 2015;Ozyurt et al 2014;Pazhanisamy et al 2011;Tartier et al 2007;Tian et al 2015;Weyemi et al 2015;Winyard et al 1992;Yang et al 2007bYang et al , 2005, while inhibiting NO in particular inhibits DNA damage and mutations in bystander cells (Han et al 2010;Tartier et al 2007;Yang et al 2007b;Zhou et al 2008). Antioxidant activity also reduces the inflammatory response to IR in animals and cultured skin cells (Berruyer et al 2004;Das et al 2014;Ezz et al 2018;Haddadi et al 2017;Khan et al 2015;Ozyurt et al 2014;Sinha et al 2011Sinha et al , 2012Zetner et al 2016;Zhang et al 2017) and the epigenetic effects of IR in vitro (Bernal et al 2013;Kloypan et al 2015;Simone et al 2009). RONS also drives proliferation directly (Han et al 2010) and via cell death and compensatory proliferation following damage to DNA and important cellular macromolecule...…”
Section: Essentiality Of Ronsmentioning
confidence: 99%
“…Ginkgo biloba extract and other traditional Chinese medicines can reduce damage and promote cell growth (21) . In another study, the radioprotective potential of tomato seed oil in adult male rats exposed to γ-rays was demonstrated (22) . In addition, a recent study reported that melatonin not only has the function of anti-oxidation, but also has the effect of radiation protection.…”
Section: Discussionmentioning
confidence: 96%
“…Ezz and coworkers irradiated rats with γ radiation, which induced oxidative stress along with a sharp rise in testicular MDA levels. It also reduced the SOD activity and serum testosterone levels [ 173 ]. Moreover, when mice were irradiated with 0.258 Gy X-ray twice a day for 4 days a week, it resulted in elevated ROS levels, lipid peroxidation, serum lactate dehydrogenase (LDH) activity, along with a reduction in testicular glutathione concentration.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Ionizing radiation can cause accumulation of collagen in the penile tissues, loss of smooth muscle and even induce fibrosis [ 170 ] and downregulate steroidogenic and spermatogenic activities [ 173 ]. Radiation in the prostate causes an upregulation of NADPH oxidase subunits gp91phox and Nox4 that result in forming ROS in the penile shaft and oxidative stress due to the imbalance between ROS and Nrf2 protein [ 171 , 175 ].…”
Section: Environmental Factorsmentioning
confidence: 99%